Structural and Mechanical Properties of Non-Glazed Ceramic Tiles Developed from Selected Mineral Deposits in Uganda - Mukwaya, George William; Enjiku, Ben; Panzi Mukhokosi, Emma (Nano-Horizons: Journal of Nanosciences and Nanotechnologies, 2023)
Uganda is well endowed with clay resources; however, comprehensive knowledge about the composition, structure and suitability of these clays for ceramic tile production is lacking. In this study, we provide a comprehensive characterisation of locally sourced clays in Uganda and their suitability for ceramic tile production. In the study, we developed ceramic tiles using feldspar, kaolin, ball clay and sand from four different sites in Uganda. We focused on analysing the surface morphology, crystallographic structure and mineralogical composition of the raw materials. In addition, we examined the mechanical properties of the developed tiles with the different mixture ratios of the clay types. The surface morphology of the raw materials was analysed by using a scanning electron microscope. The structural analysis of the raw clay materials was done using X-ray diffraction. The mineralogical composition of the raw materials was investigated using energy dispersive X-ray spectroscopy and X-ray fluorescence spectroscopy. The results indicated that the strength and rapture modulus are influenced by the composition of kaolin and feldspar. We concluded that the selected mineral deposits can be used in the production of ceramic tiles in Uganda.